2015
DOI: 10.1016/j.irfa.2015.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Comparing U.S. and European market volatility responses to interest rate policy announcements

Abstract: We examine the response of U.S. (VIX) and German (VDAX) implied volatility indices to the announcement of interest rate policy decisions by the Federal Open Market Committee (FOMC) and the European Central Bank (ECB). We confirm prior findings that VIX declines on FOMC meetings days. We present new findings that indicate that VDAX declines on FOMC meeting days, but is not related to ECB meeting days. VIX is unrelated to ECB meeting days. Taken collectively, our results indicate a prominent position for the FOM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…A study on the US and German markets by Krieger et al (2015) considered the reactions to interest rate announcements in terms of implied volatility. The authors reported that volatility in the US market tends to abate in response to scheduled announcements, irrespective of the degree to which the announcements are in line with expectations.…”
Section: Interest Ratesmentioning
confidence: 99%
“…A study on the US and German markets by Krieger et al (2015) considered the reactions to interest rate announcements in terms of implied volatility. The authors reported that volatility in the US market tends to abate in response to scheduled announcements, irrespective of the degree to which the announcements are in line with expectations.…”
Section: Interest Ratesmentioning
confidence: 99%
“…They found that after the FOMC meeting, the VIX index fell by an average of 2%. Krieger et al [28] compared the response of the US VIX index and the German VDAX index. Fernandez-Perez et al [29] found that the VIX index began to decline immediately after the FOMC announcement.…”
Section: Literature Reviewmentioning
confidence: 99%